2015
DOI: 10.1021/acs.jpcb.5b01983
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding to the Silica Surface

Abstract: We investigate the DNA-silica binding mechanism using molecular dynamics simulations. This system is of technological importance, and also of interest to explore how negatively charged DNA can bind to a silica surface, which is also negatively charged at pH values above its isoelectric point near pH 3. We find that the two major binding mechanisms are attractive interactions between DNA phosphate and surface silanol groups and hydrophobic bonding between DNA base and silica hydrophobic region. Umbrella samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 110 publications
1
87
1
Order By: Relevance
“…In the case of the ssDNA adsorbed onto the SWCNTs, the N:P ratio remains constant while the amount of N increases relative to C. This indicates that the ssDNA remains adsorbed and the carbon lost was probably amorphous or adventitious carbon. The strong adsorption of ssDNA to SWCNTs is supported by various theoretical studies and its strong adsorption to other substrates …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the ssDNA adsorbed onto the SWCNTs, the N:P ratio remains constant while the amount of N increases relative to C. This indicates that the ssDNA remains adsorbed and the carbon lost was probably amorphous or adventitious carbon. The strong adsorption of ssDNA to SWCNTs is supported by various theoretical studies and its strong adsorption to other substrates …”
Section: Resultsmentioning
confidence: 99%
“…Prior to investigating ssDNA desorption from SWCNTs, ssDNA adsorption was investigatedt ob oth confirm adsorption and to determine baseline values for characterizing subsequent desorption. (GT) 20 was chosen as the model ssDNA oligomer because it has been used for the chirality-specifics eparation of SWCNTsa nd because we have found that longer ssDNA strandsy ield ah igher concentration of SWCNT in suspension after probe sonication and centrifugation (typical optical density x dilution factor 20-30, see Figure S1 in the Supporting Information). [5b] The photographs of the suspension in Figure 1(a) shows the produced SWCNT suspension was stable (for months) and recorded azeta potential of À42 mV,which is similar to other reports of CNT-DNA suspensions and similar in magnitude to SWCNT suspensions with anionic surfactant sodium deoxycholate ( Figure S2).…”
Section: Adsorption Of Ssdnamentioning
confidence: 99%
“…Note that it has been demonstrated by molecular dynamics simulations that DNA can still bind to a (a negatively charged) silica surface effectively and the repulsion between silica and DNA can be weak due to the screening effect of the counterions near both surfaces. 71 Furthermore, the DNA binding to silica nanoparticles also has been detected experimentally in a salt-free solution at pH ¼ 7. 72 The details of surface modification are described in the supplementary material.…”
Section: Surface Modificationmentioning
confidence: 96%
“…Thus, to provide insight into important issues such as the mechanism behind DNA binding to silica is of great interest. Using molecular dynamics simulations, Shi et al (2015) showed that the two major mechanisms for binding of DNA to silica are attractive interactions between DNA phosphate and surface silanol groups and hydrophobic bonding between DNA base and hydrophobic region of silica surface. These short-range attractions can be sufficiently strong to overcome the electrostatic repulsion between negatively charged DNA and negatively charged silica surface.…”
Section: Detection Of Pathogenic Virusesmentioning
confidence: 99%